Accuracy of estimating Unicondylar Knee Replacement implant varus/valgus angles from antero-posterior radiographs. Issue 1 (1st January 2016) - Khare, Rahul; Jaramaz, Branislav
Abstract: Unicondylar Knee Replacement (UKR) is an orthopedic surgical procedure to reduce pain and improve function in the knee. Load-bearing long-standing antero-posterior (AP) radiographs are typically used postoperatively to measure the leg alignment and assess the varus/valgus implant orientation. However, implant out-of-plane rotations, user variability, and X-ray acquisition parameters introduce errors in the estimation of the implant varus/valgus estimation. Previous work has explored the accuracy of various imaging modalities in this estimation. In this work, we explored the impact of out-of-plane rotations and X-ray acquisition parameters on the estimation of implant component varus/valgus angles. For our study, we used a single CT scan and positioned femoral and tibial implants under varying orientations within the CT volume. Then, a custom software application was used to obtain digitally reconstructed radiographs from the CT scan with implants under varying orientations. Two users were then asked to manually estimate the varus/valgus angles for the implants. We found that there was significant inter-user variability ( p < 0.05) in the varus/valgus estimates for the two users. However, the 'ideal' measurements, obtained using actual implant orientations, showed small errors due to variations in implant orientation. We also found that variation in the projection center does not have a statistically significant impact ( p < 0.01) on the estimation of implant varus/valgus angles. We conclude that manual estimates of UKR implant varus/valgus orientations are unreliable.